Remediation of Sexual Violence of The New Order Regime in The Film of Seperti Dendam Rindu Harus Dibayar Tuntas - Laillia Dhiah Indriani (Seni Media Rekam ISI Surakarta, 2023)
Sexual violence has become a hot topic of discussion recently. However, it didn’t just happen; sexual violence has roots in a long history in Indonesia. Every regime has its narrative of sexual violence, and the New Order regime is no exception. The New Order, often labeled as a military and violent regime, could not detach itself from the